1991
DOI: 10.1002/ps.2780330308
|View full text |Cite
|
Sign up to set email alerts
|

DDT‐membrane interactions studied with two fluorescent probes

Abstract: The effects of DDT (0‐100 μM) in pure phospholipid and phospholipid/cholesterol bilayers were investigated by fluorescence polarization of 1,6‐diphenyl‐1,3,5‐hexatriene (DPH), a probe located in the bilayer interior, and by excimer to monomer fluorescence intensity ratio (I′/I) of 1,3‐di(l‐pyrenyl)propane (Py(3)Py), a probe sitting closer to the polar region. In the gel phase of dimyristoylphosphatidylcholine (DMPC) bilayers, DDT induces concentration‐dependent fluidizing effects into the hydrophobic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…At the experimental temperature of 37 "C, DPPC is in the ripple phase (see Table 1) and shows the highest membrane-water partition coefficients in our experiments, probably due to larger holes that are present in the bilayer. In the work of Antunes et al, it can also be seen that the partitioning of DDT into DMPC vesicles is the highest at 24 "C where DMPC is in the ripple phase (11). At any definite temperature, phospholipids have a particular fluidity dependent on their phase main transition temperature.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At the experimental temperature of 37 "C, DPPC is in the ripple phase (see Table 1) and shows the highest membrane-water partition coefficients in our experiments, probably due to larger holes that are present in the bilayer. In the work of Antunes et al, it can also be seen that the partitioning of DDT into DMPC vesicles is the highest at 24 "C where DMPC is in the ripple phase (11). At any definite temperature, phospholipids have a particular fluidity dependent on their phase main transition temperature.…”
Section: Resultsmentioning
confidence: 95%
“…It is believed that general anesthetic toxicological effects of hydrophobic compounds are the result of compound-membrane interactions (9,10). The biochemical aspects of these interactions are poorly understood, but it is suggested that hydrophobics inserted in the membrane can alter the membrane fluidity and so interfere with biological functions of the membrane (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Chem. 17,1998 W.J. Dulfer et al The conductivity of the Caco-2 cell monolayer to PCB transport from the apical membrane to the basolateral compartment can be calculated following Equation 4, D trans ϭ N trans / (f ap Ϫ f baso ), where (f ap Ϫ f baso ) denotes the difference in fugacity between the apical and the basolateral compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Rahman and Barrowman [15] showed that for the uptake of PAHs with very low aqueous solubilities, the unstirred water layer forms the major resistance, and the bioavailability of these chemicals was enhanced significantly by incorporation in bile salt micelles. High affinities of various chlorinated hydrocarbons and the hydrophobic pesticide dichlorodiphenyltrichloroethane (DDT) to membrane vesicles were observed by Omann and Lackowicz and by Antunes‐Madeira et al, respectively [16,17]. The high solubilization capacity of lipoproteins for hydrophobic contaminants is supported by the observation that lipoproteins form the major binding site in hepatic cytosol and transport vehicle in the plasma for hydrophobic xenobiotics [18–20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation